Analisis Sufiks Penanda Biaya -Chin (賃) dan -Dai (代) dalam Bahasa Jepang - Akbar Al Azhar, Wira; Aibonotika, Arza; Budiani, Dini (Jurnal Bahasa Jepang Taiyou, 2024)
The meaning of the word 'cost' in Japanese can be expressed with the suffix kanji -chin (賃), and -dai (代), if these two kanji are placed at the end or end the vocabulary. However, to determine which vocabulary is included in this suffix, it will be very difficult to determine which suffix is most appropriate in its use. Therefore, this research aims to determine the characteristics, meaning and whether the suffixes meaning costs can replace each other. There are many influences that can occur, such as the image or impression of the vocabulary, vocabulary that is not used every day or because the vocabulary is no longer used, etc. This research uses a qualitative descriptive method with morphosemantic studies.